HISTOPATHOLOGICAL FINDINGS IN PATIENTS WITH ULTRASONOGRAPHICALLY DETECTED ENDOMETRIAL POLYP - Bekim Dika; Kocevska, Ana; Kristina Skeparovska; Ivan Koprivnjak (Македонско лекарско друштво = Macedonian medical association, 2025)
Introduction. Endometrial polyps are defined as the excess hyperplastic growth of endometrial glands and stroma within the uterine cavity. They vary in size from a few millimeters to several centimeters. Polyps may be found as a single lesion or multiple lesions filling the entire endometrial cavity. Endometrial polyps may be diagnosed at all ages but the highest incidence is between 40 - 49 years of age. They are considered benign but there is a small risk of malignant transformation. Thе aim of this study is to determine the correlation between the ultrasound findings of endometrial polyp and the histopathological reports. Material and methods. We analized a total of 140 histopathological reports from patients who underwent fractionated explorative curettage or hysteroscopy due to ultrasonographically diagnosed endometrial polyps. The histopathological findings showed that in 112 (80%) the diagnosis of endometrial polyp was confirmed and 78 of these were hyperplastic polyps (69.6% of the total number of endometrial polyps), 5 polyps with atypical hyperplasia (4.5%), 1 (0.9%) malignant polyp (adenocarcinoma), 5 senile polyps (4,5%). Endocervical or isthmicocervical polyp were diagnosed in 12 patients (8.6%). The remaining 28 patients (20%) had these findings: simplex endometrial hyperplasia without atypia (6 patients), complex endometrial hyperplasia without atypia (1), complex endometrial hyperplasia with atypia (1 patient), submucosal myoma (3), adenomyoma (1), prolonged and inadequate estrogen action (8), deficient secretory phase (3), chronic cervicitis (3), and normal endometrium in 2 patients. Conclusion: Transvaginal ultrasound is the first line of investigation while evaluating the endometrium. Its accuracy is limited in the diagnosis of focal endometrial lesions, so the further investigation is needed. Hysteroscopy is the gold standard for accurate evaluation of intracavitary pathology like submucous fibroid, polyps or anomalies.
Keywords: endometrial polyp; ultrasound; curettage; hysteroscopy; histopathological